2017
DOI: 10.3389/fnagi.2017.00382
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Enhanced Executive Function in Older Video Game Players: An fMRI Study

Abstract: Video games have been found to have positive influences on executive function in older adults; however, the underlying neural basis of the benefits from video games has been unclear. Adopting a task-based functional magnetic resonance imaging (fMRI) study targeted at the flanker task, the present study aims to explore the neural basis of the improved executive function in older adults with video game experiences. Twenty video game players (VGPs) and twenty non-video game players (NVGPs) of 60 years of age or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…goaldirected neural process) [37]. Even older players showed increased activation in right dorsolateral PFC (DLPFC) [38]. Taken together, VG playing, especially AVG playing, is associated with the enhancement of visual attention that takes an important role in the efficient processing of information [39].…”
Section: Sgsmentioning
confidence: 99%
“…goaldirected neural process) [37]. Even older players showed increased activation in right dorsolateral PFC (DLPFC) [38]. Taken together, VG playing, especially AVG playing, is associated with the enhancement of visual attention that takes an important role in the efficient processing of information [39].…”
Section: Sgsmentioning
confidence: 99%
“…Recent studies using MRI technique for brain imaging have demonstrated video gaming effects on neuroplasticity. Earlier imaging studies using cross-sectional and longitudinal methods have shown that playing video games affects the brain structure by changing the grey matter [31,32,33], white matter [34,35], and functional connectivity [36,37,38,39]. Additionally, a few intervention studies have demonstrated that playing video games changed brain structure and functions [40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the retention of the adaptive effect of video gaming on brain development still remains unclear. Second, experimental research has usually exposed participants to a video gaming session and examined how an increase in video gaming time improved brain development (Mishra et al, 2011; Wu et al, 2012; Wang et al, 2017). However, to the best of our knowledge, research has not yet examined whether a decrease in brain development is observable after players have reduced their video gaming time over an extended period of time.…”
Section: Introductionmentioning
confidence: 99%